Glycine neurotransmission: Its role in development - Salceda, Rocío (Frontiers in Neuroscience, 2022)
The accurate function of the central nervous system (CNS) depends of the consonance of multiple genetic programs and external signals during the ontogenesis. A variety of molecules including neurotransmitters, have been implied in the regulation of proliferation, survival, and cell-fate of neurons and glial cells. Among these, neurotransmitters may play a central role since functional ligand-gated ionic channel receptors have been described before the establishment of synapses. This review argues on the function of glycine during development, and show evidence indicating it regulates morphogenetic events by means of their transporters and receptors, emphasizing the role of glycinergic activity in the balance of excitatory and inhibitory signals during development. Understanding the mechanisms involved in these processes would help us to know the etiology of cognitive dysfunctions and lead to improve brain repair strategies.